2020
DOI: 10.3389/fninf.2020.596340
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Factors of Human Carotid Atherosclerotic Plaque Rupture, by Calculating Stress/Strain in the Plaque, Based on CEUS Images: A Numerical Study

Abstract: Carotid plaque neovascularization is one of the major factors for the classification of vulnerable plaque, but the axial force effects of the pulsatile blood flow on the plaque with neovessel and intraplaque hemorrhage was unclear. Together with the severity of stenosis, the fibrous cap thickness, large lipid core, and the neovascularization followed by intraplaque hemorrhage (IPH) have been regarded as high-risk features of plaque rupture. In this work, the effects of these factors were evaluated on the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
(72 reference statements)
2
5
0
Order By: Relevance
“…Related studies have illustrated that neovascularization and hemorrhage in plaque increase the pressure in plaque. 33 This also confirmed the conclusion of previous research of which the limitation of carotid stenosis in evaluating the occurrence of stroke and the importance of assessing the internal composition and morphological changes of large artery stroke. 37,38 In the current study, we observed that the subharmonic gradient of intraplaque was relatively larger in the IS group, and the threshold value of 3.95 dB was obtained, with specificity of about 77.27% and sensitivity of about 66.67%, which provides a new way for us to quantitatively monitor the pressure in plaque.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Related studies have illustrated that neovascularization and hemorrhage in plaque increase the pressure in plaque. 33 This also confirmed the conclusion of previous research of which the limitation of carotid stenosis in evaluating the occurrence of stroke and the importance of assessing the internal composition and morphological changes of large artery stroke. 37,38 In the current study, we observed that the subharmonic gradient of intraplaque was relatively larger in the IS group, and the threshold value of 3.95 dB was obtained, with specificity of about 77.27% and sensitivity of about 66.67%, which provides a new way for us to quantitatively monitor the pressure in plaque.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, the high‐pressure difference on the plaque surface may induce the plaque to break easily. Related studies have illustrated that neovascularization and hemorrhage in plaque increase the pressure in plaque 33 . This also confirmed the conclusion of previous research of which the limitation of carotid stenosis in evaluating the occurrence of stroke and the importance of assessing the internal composition and morphological changes of large artery stroke 37,38 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Apoptosis and necrosis of the foam cells leads to the build-up of a lipid-rich necrotic core (LRNC). Plaque neovessels support the entry of more monocytes into the plaque, however, these vessels are fragile, which could cause intraplaque hemorrhage (IPH) ( 14 ). Also fissures or disruption of the fibrous cap (FC) may contribute to the development of IPH ( 15 ).…”
Section: Introductionmentioning
confidence: 99%